Aberrant Inter-hemispheric Connectivity in Patients With Recurrent Major Depressive Disorder: A Multimodal MRI Study - Zheng, Guo; Yingli, Zhang; Shengli, Chen; Zhifeng, Zhou; Bo, Peng; Gangqiang, Hou; Yingwei, Qiu (Frontiers in Neurology, 2022)
Objective: Inter-hemispheric network dysconnectivity has been well documented in patients with recurrent major depressive disorder (MDD). However, it remains unclear how structural networks impairment between bilateral hemispheres relates to inter-hemispheric functional dysconnectivity and depression severity in MDD. Our study attempts to characterize interhemispheric structural and functional connectivity as well as their relationship with disease severity in patients with recurrent major depressive disorder (MDD). Materials and Methods: Resting-state functional MRI (fMRI), high-resolution anatomical images and diffusion tensor MRI of the whole brain were performed in 140 MDD patients and 44 normal controls matched for age, sex, years of education. We compared macrostructural as well as microstructural integrity of corpus callosum (CC) and its five subregion and voxel-mirrored homotopic functional connectivity (VMHC) between the two groups. Depressive severity was assessed using 17-term Hamilton Depression Rating Scale (HDRS). Abnormal CC subregions integrity and VMHC revealed by group comparison were extracted and correlated with HDRS. Results: Compared with control subjects, MDD patients had significantly attenuated inter-hemispheric homotopic FC in the bilateral medial prefrontal cortex, and impaired anterior CC microstructural integrity (each comparison had a corrected P < 0.05), whereas CC macrostructural measurements remained stable. In addition, disruption of anterior CC microstructural integrity correlated with a reduction in FC in the bilateral medial prefrontal cortex, which correlated with depression severity in MDD patients. Furthermore, disruption of anterior CC integrity exerted an indirect influence on depression severity in MDD patients through an impairment of inter-hemispheric homotopic FC. Conclusion: These findings may help to advance our understanding of the neurobiological basis of depression by identifying region-specific interhemispheric dysconnectivity.